Nilai-Nilai Pendidikan Anti Korupsi Dalam Kearifan Lokal Masyarakat Bali - Ni Luh Gede Hadriani (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
Since the first, the Indonesian government has taken various actions to eradicate corruption, but it turns out that corruption tends to exist and continues to increase both in quantity and quality. The disease of corruption that afflicts our nation cannot be left alone, a solution must be found, namely by exploring the values of anti-corruption education that exist in the local wisdom of the Balinese people, such as; the value of honesty, namely the teachings of Tri Kaya Pari Sudha (think good, say good and do good). Purusa Artha's chess teachings also teach to behave honestly in seeking Artha (wealth), discipline, namely the voice of the kulkul which means calling the community to come on time, courage, which is mesantalan activities, justice, namely the same teachings, different, funds and danda, hard work is there feeling embarrassed, independence, namely the teachings of swadharma, caring, namely the teachings of tatwamasi, simplicity. Keywords: Anti-Corruption Educational Values and Local Wisdom